Is it worth to explore the contralateral side in unilateral childhood inguinal hernia?: A PRISMA-compliant meta-analysis. Issue 31 (31st July 2020) - Staerkle, Ralph F.; Guglielmetti, Laura C.; Bielicki, Isabella N.; Gaukel, Stefan; Frongia, Giovanni; Hilton, Sarah; Fink, Lukas; Vuille-dit-Bille, Raphael N.
Abstract: Background: It is still not clear if the contralateral side should be explored in children with unilateral inguinal hernias. The primary aim of the present study was to assess the incidence of metachronous contralateral inguinal hernias (MCIHs) in the pediatric population. The second aim was to assess factors associated with increased risk of MCIH development. Methods: Prospective studies including patients from 0-19 years undergoing unilateral inguinal hernia repair without surgical exploration of the contralateral side between 1947 and April 2020 with a minimal follow-up of one year were searched. Searches included EMBASE, MEDLINE, and the Cochrane Central Register of Controlled Trials. Results: Seven studies involving 1774 children (1452 boys (82%) and 322 girls (18%) were identified. Overall the incidence of MCIH was 6%. Incidence of MCIH development was significantly higher in children with initial left-sided (9%) versus right-sided (3%) hernia (OR 2.55 with 95% CI from 1.56 to 4.17; P  = 0.0002), in female (8%) versus male (4%) children (OR 1.74 with 95% CI from 1.01 to 3.01; P  = 0.0469) and in patients with open (14%) versus closed (3%) contralateral processus vaginalis (CPV) (OR 4.17 with 95% CI from 1.25 to 13.9; P  = 0.0202). There was no significant difference in MCIH development depending on follow-up duration (follow-up of ⩽2 years (i.e. 1–2 years): calculated MCIH incidence 5% (95% CI from 0.00 to 0.11%; 3 studies; 569 patients), follow-up of ≥3 years (i.e. 3–4 years): 6% (95% CI from 0.03 to 0.09; 3 studies, 983 patients)) or patients' age (MCIH incidence in children <1 year: 6.9%; older children: 4.5%; OR 1.87 with 95% CI from 0.97 to 3.62; P  = 0.0618). Conclusions: Overall incidence of MCIH development is 6%. Initial left-sided hernia, female gender and open CPV are risk factors for MCIH development.